Nano Freezing–Thawing of Atlantic Salmon Fillets: Impact on Thermodynamic and Quality Characteristics - Wenxuan Wang; Wenzheng Li; Ying Bu; Xuepeng Li; Wenhui Zhu (Foods, 2023)
The presence of magnetic nanoparticles (MNPs) suppresses ice nucleation and growth during freezing and thawing. In this study, the effects of MNPs-assisted cryogenic freezing integrated with MNP-combined microwave thawing (NNMT) on the thermodynamic and quality changes of salmon fillets were investigated. Results have shown that NNMT raises Tg (glass transition temperature) and Tmax (transition temperature), thus improving the storage stability of salmon fillets. MNPs-assisted freezing and thawing treatment, especially NNMT treatment, significantly improved the water holding capacity, texture, color, and other quality characteristics of salmon fillets. In addition, the lipid and protein oxidation degrees of the NNMT treatment were the lowest, while the myofibrillar protein solubility of NNMT was the highest (87.28%). This study demonstrated that NNMT has minimal impact on the freezing–thawing quality of salmon fillets, making it a more suitable option for the preservation of aquatic foods.